2017
DOI: 10.1111/jog.13484
|View full text |Cite
|
Sign up to set email alerts
|

Platelet indices in preterm premature rupture of membranes and their relation with adverse neonatal outcomes

Abstract: Aim: Preterm premature rupture of membranes (PPROM) is not only the most common distinguishable cause of preterm delivery, but is also associated with adverse neonatal outcomes. We determined the platelet indices in PPROM cases and evaluated their relationship to adverse neonatal outcomes. Methods: Fifty patients with PPROM and 50 patients who experienced spontaneous preterm labor at < 37 gestational weeks were evaluated. Complete blood counts, birth weights, Apgar scores, presence of sepsis and respiratory di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 33 publications
3
10
0
2
Order By: Relevance
“…The effectiveness of using platelet indices to predict preterm labor has also been studied. Gioia [15]. The results of our study are in line with Dundar et al We found that platelet count and MPV before the second trimester were significantly higher in women who went on to experience PPROM than in those who did not.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The effectiveness of using platelet indices to predict preterm labor has also been studied. Gioia [15]. The results of our study are in line with Dundar et al We found that platelet count and MPV before the second trimester were significantly higher in women who went on to experience PPROM than in those who did not.…”
Section: Resultssupporting
confidence: 92%
“…Mean platelet volume (MPV) can be used reliably to gauge platelet size, which indicates their function and activation. An association between both prothrombosis and proinflammation has been found [14], but research on the early predictive value of MPV and platelet count for PPROM is insufficient [9,15]. With this gap in the literature and given the established link between subclinical intrauterine infection and PPROM mechanisms, there is a need to examine the role of MPV and platelet count in PPROM.…”
Section: Introductionmentioning
confidence: 99%
“…In contrary Dundar B, et al [14] showed that mean Neutrophil count in patients was 8. The only difference is the significance of CRP found in that study which because they did not exclude the cases with clinical chorioamnoitis, and of course all the biomarkers increase in clinical chorioamnoitis.…”
Section: Discussionmentioning
confidence: 89%
“…These observations are in agreement with our finding of higher cord hematocrit associated with lower birthweights and head circumference, but contrast with the negative association of cord platelet counts with head circumference. There is evidence that an increased production and activation of platelets during pregnancy occur during inflammatory processes leading to platelet consumption and to a hypercoagulable state that impacts placental micro-circulation and placental insufficiency 70 . Also, we had previously shown that higher plateletcrit was associated with higher C-reactive protein in pregnant and lactating Ngäbe women 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Estas observaciones están de acuerdo con nuestros hallazgos de un hematocrito en sangre de cordón más alto asociado con menor peso al nacer y circunferencia cefálica, pero contrasta con la asociación de mayor conteo de plaquetas en sangre de cordón y menor circunferencia cefálica. Existe evidencia de que durante procesos inflamatorios en el embarazo se desarrolla un aumento en la producción y activación plaquetarias, llevando a un consumo de plaquetas y a un estado pro-coagulante que impacta en la microcirculación placentaria produciendo insuficiencia 70 . También, hemos mostrado previamente que un plaquetocrito mayor se asoció con una PCR más alta en mujeres embarazadas y lactantes Ngäbe 24 .…”
Section: Discussionunclassified